Photocatalytic reduction of carbon dioxide using iodine-doped titanium dioxide with high exposed {001} facets under visible light. Issue 28 (29th February 2016) - He, Zhiqiao; Yu, Yan; Wang, Da; Tang, Juntao; Chen, Jianmeng; Song, Shuang
Abstract : Iodine-doped titanium dioxide nanosheets with high exposed {001} facets (IFTO) were synthesized by a two-step hydrothermal treatment followed by calcination at 350 °C. Abstract : Iodine-doped titanium dioxide nanosheets with high exposed {001} facets (IFTO) were synthesized by a two-step hydrothermal treatment followed by calcination at 350 °C. The photocatalyst samples were characterized by X-ray diffractometry, transmission electron microscopy, field emission scanning electron microscopy, ultraviolet-visible diffuse reflectance spectra, Brunauer–Emmett–Teller measurements and X-ray photoelectron spectroscopy. The IFTO were more active than surface-fluorinated TiO2 nanosheets or iodine-doped TiO2 nanoparticles in the gaseous reduction of CO2 with water vapor. The IFTO photocatalytic activity was repeatable over five successive cycles. Coexisting I–O–Ti and I–O–I structures in the IFTO TiO2 lattice contributed to visible light absorption and a high percentage of exposed {001} facets that enhance H2 O oxidation. Surface fluorination promoted the formation of unsaturated Ti atoms, which helped reduce CO2 to CO2 − and retard the recombination of photogenerated electron–hole pairs.